Hans Jonas' Integrative Philosophy of Life as a Foothold for Integrative Bioethics - Jurić, Hrvoje, filozof (Array, 2011)
European approach to bioethical problems – which is developed before or parallel to the "official emergence" of bioethics in 1960s and 1970s – emphasizes a need for the widened and deepened consideration of the very notion of life, which should be taken in account when speaking about ethical dimensions of manipulation with the life at different levels. It could be traced in the works of Fritz Jahr, Albert Schweitzer, Georg Picht, Klaus Michael Meyer-Abich and especially Hans Jonas (1903–1993). In that sense, we should take into consideration not only Jonas' ethics of responsibility, developed in the late phase of his life and formulated in the philosophical bestseller Das Prinzip Verantwortung, but also his long-term research of Gnostic religion and thought, as well as his attempt to establish the philosophical biology as a new philosophy of the human, nature and life. Jonas developed the integrative philosophy of life in which centre stands ethically connotated philosophy of nature, based both on the results of contemporary natural sciences and theological speculations. In this presentation I will try to show how the synergy of evolutionist-biological, teleological-philosophical and religious-theological approaches contributes to the decryption of the notion of life, i.e. to establishing the integrative philosophy of life which implies respect and responsibility for the nature and life in general. Jonas' integrative philosophy of life shows us clearly what pluri-perspectivity and integrativity in bioethics actually mean, because it is far from any reductionism and tries to include different scientific and non-scientific perspectives, offering at the same time a platform for their dialogical mediation.